1990
DOI: 10.1111/j.1365-2621.1990.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental and Sensory Evaluation of Textural Properties of Extrudates from Blends of High Starch/High Protein Fractions of Dry Beans

Abstract: A Wenger X5 single-screw extruder was used to produce bean extrudates from formulations modified by addition of high protein bean fraction or hull. The effect of process temperature was investigated. The higher the process temperature, the lower was the sample stress and the higher the sensory score for crispness. Product processed below 121°C was unacceptable. Crispness was good for samples containing 13-16% protein or 17-21% fiber; outside these ranges the extrudates were too hard. Shear stress increased uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
4
13
0
3
Order By: Relevance
“…soy flour, temperature and time had important roles to play in the OAA of the product. This finding was in accordance with the study reported by Skierkowski, Gujska, and Khan (1990). They carried out instrumental and sensory evaluation of textural properties of extrudates from blends of high starch/high protein fractions of dry beans.…”
Section: Effect Of Process Conditions On Overall Acceptabilitysupporting
confidence: 94%
“…soy flour, temperature and time had important roles to play in the OAA of the product. This finding was in accordance with the study reported by Skierkowski, Gujska, and Khan (1990). They carried out instrumental and sensory evaluation of textural properties of extrudates from blends of high starch/high protein fractions of dry beans.…”
Section: Effect Of Process Conditions On Overall Acceptabilitysupporting
confidence: 94%
“…temperature, time, initial moisture content and air velocity had important roles to play in the OAA of the product. This finding was in accordance with the study reported by Skierkowski, Gujska, and Khan (1990). They carried out instrumental and sensory evaluation of textural properties of extrudates from blends of high starch/high protein fractions of dry beans.…”
Section: Overall Acceptability (Oaa)supporting
confidence: 94%
“…soy flour, temperature and time had important roles to play in the OAA of the product. This finding was in accordance with the study reported by Skierkowski et al (1990). The authors carried out instrumental and sensory evaluation of textural properties of extrudates from blends of high starch/ high protein fractions of dry beans.…”
Section: Effect Of Process Conditions On Overall Acceptability (Oaa)supporting
confidence: 92%